DDX58 expression promotes inflammation and growth arrest in Sertoli cells by stabilizing p65 mRNA in patients with Sertoli cell-only syndrome - Sun, Hao; Yang, Zhan; Teng, Zhihai; Zhang, Yanping; Han, Zhenwei; Xu, Chao; Wang, Zhu; Wang, Hu; Wen, Hongzhuang; Chen, Xiaodong; Qu, Changbao; Wang, Yaxuan (Frontiers in Immunology, 2023)
Sertoli cell -only syndrome (SCOS) is a type of testicular pathological failure that causes male infertility and no effective treatment strategy, is available for this condition. Moreover, the molecular mechanism underlying its development remains unknown. We identified DExD/H-Box helicase 58 (DDX58) as a key gene in SCOS based on four datasets of testicular tissue samples obtained from the Gene Expression Synthesis database. DDX58 was significantly upregulated in SCOS testicular Sertoli cells. Moreover, high expression of DDX58 was positively correlated with the expression of several testicular inflammatory factors, such as IL -1β, IL-18, and IL-6. Interestingly, DDX58 could be induced in the D-galactose (D-gal)-stimulated TM4 cell injury model. Whereas silencing of DDX58 inhibited D-gal -mediated p65 expression, inflammatory cytokine release, and growth arrest. Mechanistically, we found that DDX58 acts as an RNA-binding protein, which enhances p65 expression by promoting mRNA stability. Furthermore, p65 gene silencing decreased the expression of inflammatory cytokines and inhibition of cell growth in D-gal-induced cells. In conclusion, our findings demonstrate that DDX58 promotes inflammatory responses and growth arrest in SCOS Sertoli cells by stabilizing p65 mRNA. Accordingly, the DDX58/p65 regulatory axis might be a therapeutic target for SCOS.